2003
DOI: 10.1086/375683
|View full text |Cite
|
Sign up to set email alerts
|

A Major Soft Gamma Repeater-like Outburst and Rotation Glitch in the No-longer-so-anomalous X-Ray Pulsar 1E 2259+586

Abstract: We report a major outburst from the anomalous X-ray pulsar 1E 2259ϩ586, in which over 80 X-ray bursts were detected in 4 hr using the Rossi X-Ray Timing Explorer. The bursts range in duration from 2 ms to 3 s and have fluences in the 2-10 keV band that range from to ergs cm Ϫ2. We simultaneously observed Ϫ11 Ϫ93 # 10 5 # 10 increases of the pulsed and persistent X-ray emission by over an order of magnitude relative to quiescent levels. Both decayed significantly during the course of our 14 ks observation. Corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
142
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(154 citation statements)
references
References 25 publications
11
142
0
1
Order By: Relevance
“…than the ones of SGR 0418+5729 and SGR 1822-1606, indicating that 1E 2259+586 is a very active source in which glitches and outburst activity, such as those observed in 2002 (Kaspi et al 2003;Woods et al 2004), can occur with relatively high frequency. It is interesting to note that glitches of minor intensity |ΔP|/P 10 −7 can be even more frequent, with recurrence times of 4 yr.…”
Section: Solidification and Glitchesmentioning
confidence: 92%
“…than the ones of SGR 0418+5729 and SGR 1822-1606, indicating that 1E 2259+586 is a very active source in which glitches and outburst activity, such as those observed in 2002 (Kaspi et al 2003;Woods et al 2004), can occur with relatively high frequency. It is interesting to note that glitches of minor intensity |ΔP|/P 10 −7 can be even more frequent, with recurrence times of 4 yr.…”
Section: Solidification and Glitchesmentioning
confidence: 92%
“…The detection of a ∼8 s periodicity in the decaying tail of a very intense (∼10 44 erg) and long (several minutes) event, known as giant flare, from SGR 0526-66 on 1979 March 5th (Mazets et al 1979) suggested the association of SGRs with neutron stars. A small sample of peculiar X-ray pulsars, namely the Anomalous X-ray Pulsars (AXPs) has been proposed to be closely related to SGRs based on similar properties, namely their period P (in the 5-12 s range), their period derivativeṖ (10 −10 -10 −13 s s −1 range), and X-ray bursts (Kouveliotou et al 1998;Kaspi et al 2003;Gavriil et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…1E 2259+586 has been monitored with Rossi X-ray Timing Explorer and Swift X-ray Telescope over almost the last two decades, showing a stable spin-down rate, with the exception of two spin-up glitches in 2002 [10] and 2007 [11], a timing event in 2009 [11], and this anti-glitch in 2012.…”
mentioning
confidence: 99%